Selection of a topical preparation in the basic treatment of chronic hemorrhoids - A. Ya. Ilkanich; K. Z. Zubailov; S. S. Kurbanov; A. A. Aysanov; Yu. S. Voronin; A. S. Matveeva; Z. N. Lopatskaya (Амбулаторная хирургия, 2021)
Introduction. The vast majority of recommendations for conservative treatment of patients with chronic hemorrhoids contain recommendations for the use of systemic drugs with venotonic and angioprotective properties and the use of topical drugs to treat and prevent exacerbation of the disease. The action of the main components of the topical drugs used is aimed at controlling local inflammation, implemented through various mechanisms. The choice of a drug is mainly subjective.Aim of the study. Comparative clinical evaluation of the effectiveness of topical drugs for the treatment of chronic hemorrhoids.Materials and methods. There are two treatment schemes that are distinguished by the type of the drug that is used. The main group includes patients in treatment of whom a combined preparation based on lidocaine and fluocortolone in the form of rectal suppositories manufactured by Bayer (221 (50.6%) patients) was used. In the control group – a combined preparation on the basis of tribenoside and lidocaine in the form of rectal suppositories by Recordati company (216 (49,4%) people). The rate of suppositories administration and duration of their use was 21 days. Clinical efficacy was estimated by the rate of regression of the main clinical manifestations of the disease: bleeding, pain syndrome, discomfort.Results and discussion. By the 14th day of treatment with Bayer preparation, bleeding as the main sign of disease exacerbation persisted in 15.2% (5) of the main patients against 26.7% (8) of the control group patients. Positive effect was obtained in the majority of patients with the initial prevalence of pain syndrome. On the 14th day the pain remained in 17.0% (8) patients of the main group against 27.9% (12) of the control group. Sense of discomfort was preserved in 10% (4) of the main group patients against 15.8% (6) of the control group patients. Regression of combined clinical manifestations of the disease in the comparison groups showed the fastest elimination of inflammation in the main group in 79.4% of patients against 73.0% in the control group on the 14th day of treatment.Conclusions. Thus, the use of Bayer preparation allowed ensuring the regression of the main clinical manifestations of the disease in a shorter time. This drug can be recommended for use in complex treatment of chronic hemorrhoids in everyday clinical practice.